Pengaruh Work Study Conflict Terhadap Burnout Pada Mahasiswa Bekerja - Zannuba Arifah; Citra Ayu Kumala Sari (Journal of Social, Culture, and Language, 2024)
Burnout is a condition of physical and psychological exhaustion due to work burdens or responsibilities. Working students who have dual tasks, namely academic tasks and tasks at work, are very at risk of experiencing burnout. This study aims to determine the effect of study-work conflict on psychological burnout among students who work at UIN Sayyid Ali Rahmatullah. The research uses a quantitative causality method to determine the influence of the work study conflict variable on the burnout variable. The sampling technique in this study used purposive sampling with predetermined criteria. The number of samples willing to be respondents was 100 students. The research results were processed using simple regression analysis with a sig result of 0.000 p0.05, meaning that work-study conflict had an effect on student burnout. The higher the level of work study conflict, the higher the level of burnout of working students and vice versa. Keywords: Work Study Conflict, Burnout